Students' Errors and Misconceptions in Solving Fundamental Mathematics Problem - Sari, Delsika Pramata; Saputra, Samnur; Ardywinata, Anton Azwar; Sukmawati, R. Ati; Fadhillah, Muhammad Nur (Mathematics Education Journal, 2023)
The purpose of this research was to analyze students' errors and misconceptions in solving Fundamental Mathematics problems. The research method used in this study was descriptive research with a qualitative approach. The subjects of this study consisted of 23 students who took the Fundamental Mathematics course at the Computer Education Study Program. The instrument used in this research was the Fundamental Mathematics Test. The research procedure consisted of three main stages, namely: (1) preparatory stage: learning activities were carried out in 7 meetings and the development of Fundamental Mathematics questions; (2) implementation: research subjects completed the Fundamental Mathematics Test as an effort to collect data; and (3) data analysis from students' answers to Fundamental Mathematics questions to describe student mistakes in solving Fundamental Mathematics problems. The results showed that many errors and misconceptions that occurred in each question were caused by errors in understanding and translating arithmetic symbols in solving Fundamental Mathematics problems, errors in drawing conclusions, and errors in making graphs and images. In addition, misconceptions occur when solving problems involving arithmetic symbols. Furthermore, the recommendation from this study is to develop a Fundamental Mathematics didactic design that is able to minimize student errors. DOI: https://doi.org/10.22342/jpm.17.3.21128.313-324